Effect of Organic-Based Humic Acid on Yield of Rice Grown in Heavy Metal Contaminated Soil - Reginawanti Hindersah; Antonio Yusuf; Betty Natalie Fitriatin; Triani Dewi; Dedi Nursyamsi; Mulyadi Mulyadi (Soilrens, 2022)
Application of certain fertilizer during long-term food crops production, might increase the heavy metal (HM) level in soil. An inexpensive and easy method to decrease this contaminant uptake by plants is application of humic acid (HA) which has the capacity to bind toxic substances. Pot experiment had been conducted to observe the influence of organic-based HA on the growth and yield of rice grown in soil contaminated with Cadmium and Lead. The experiment laid in Randomized Block Design with four treatments and six replications. Rice was grown in Inceptisols and treated with HA extracted from various organic matter. Control plants did not receive any HA. All plants had not shown any HM toxicity symptoms. The plant height as well as straw dry weight in HA-treated soil was no different with control plant. Various HA decreased available Cadmium and Lead in soil and in unhusked grain but did not affect yield traits. However, the reduced content of HM was also caused by soil acidity that shift to neutral during puddling. This experiment suggested that HA have a role to control HM availability in paddy soil and hence reduced their uptake by rice plants.